2016
DOI: 10.1016/s2213-2600(16)30305-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics, practice of ventilation, and clinical outcome in patients at risk of acute respiratory distress syndrome in intensive care units from 16 countries (PRoVENT): an international, multicentre, prospective study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
118
5
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 36 publications
23
118
5
6
Order By: Relevance
“…Similar gender differences were found in the "Consortium to Evaluate Lung Edema Genetics" (CELEG) study [7]. More recently, gender differences in V T were also found for patients without ARDS, in the international observational "Practice of VENTilation in patients without ARDS" (PRoVENT) study [8], and even for patients receiving short-lasting intraoperative ventilation during general anaesthesia for surgery, in the "Local Assessment of VEntilatory management during General Anesthesia for Surgery" (LAS VEGAS) study [9]. Why is there a tendency of clinicians to adhere to protective ventilation less strictly in females; why this gender inequity?…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Similar gender differences were found in the "Consortium to Evaluate Lung Edema Genetics" (CELEG) study [7]. More recently, gender differences in V T were also found for patients without ARDS, in the international observational "Practice of VENTilation in patients without ARDS" (PRoVENT) study [8], and even for patients receiving short-lasting intraoperative ventilation during general anaesthesia for surgery, in the "Local Assessment of VEntilatory management during General Anesthesia for Surgery" (LAS VEGAS) study [9]. Why is there a tendency of clinicians to adhere to protective ventilation less strictly in females; why this gender inequity?…”
supporting
confidence: 62%
“…It could be suggested that the gender inequity in ventilator management is caused by a difference in patients' height, since females are on average 10 to 15 cm shorter than males, as also shown in LUNG SAFE (median height 160 (155 to 165) versus 170 (169 to 178) cm) [4], the CELEG study (average height 162±7 versus 177±8 cm) [7], and in the PRoVENT study (median height 155 (150 to 160) versus 167 (162 to 170) cm) [8]. The abovementioned analysis of open access de-identified data from patients with ARDS showed that patients of shorter height were least likely to receive ventilation with a low V T , probably explaining why females were at a disproportional risk of receiving non-protective, unsafe ventilation [6].…”
mentioning
confidence: 71%
“…Less than two-thirds of the patients with ARDS receive a tidal volume <8 of mL/kg PBW. In fact, the mean tidal volume size used in patients with ARDS included in this study is comparable to those of critically ill patients receiving mechanical ventilation for other causes than ARDS (20). Also, plateau pressure was measured only in 40% of the patients with ARDS, and 83% of these patients received a PEEP <12 cmH 2 O (1).…”
mentioning
confidence: 68%
“…Because of the high correlation between the variables related to pulmonary mechanics (plateau pressure, static compliance, driving pressure), only one of the variables was included in the model. Therefore, given the increasing evidence demonstrating the importance of driving pressure on outcome, it was decided to enter driving pressure into the model [23]. Backward elimination with a criterion of P < 0.05 for retention in the model was used.…”
Section: Methodsmentioning
confidence: 99%